Game Edukasi Berhitung Gorgon Adventure - Zadinsyah Fatan Zirconi; Sidhiq Andriyanto; Putri Armilia Prayesy (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Gorgon Adventure is an interactive educational game designed to support third-grade elementary students in understanding basic arithmetic concepts. This application integrates gameplay elements with mathematics learning materials, creating an engaging learning experience capable of increasing students’ motivation and interest. The development process uses the Rapid Application Development (RAD) method, which emphasizes fast cycles of design, construction, and evaluation. Based on the results of testing, the application performs optimally, as demonstrated by black-box testing that verifies all features function properly. In terms of content validity, teacher assessment indicates a 100% score categorized as highly valid, while the User Acceptance Testing (UAT) achieved 84%, categorized as highly feasible. The effectiveness of the application is also reflected in the improvement of student learning outcomes, with the average score rising from 57.33 in the pretest to 89.33 in the post-test, showing a significant enhancement in basic arithmetic skills. With its attractive interface, interactive features, and strong testing results, Gorgon Adventure can serve as an innovative, effective, and enjoyable alternative learning media for elementary school students.